An Action Research On Peer Feedback In The Croatian Primary EFL School Context - Nataša Perinčić Tičić; Anamarija Štulina (Elektronički Zbornik Radova Veleučilišta u Šibeniku)
This paper presents an action research whose aim was to implement the peer feedback activity in EFL writing in primary school contexts in Croatia. The study follows the methodology of action research conducted in five stages. The study aims to answer the following research questions: 1. Can the activity of peer feedback in writing be tailored to primary school students? 2. Can peer feedback activity be successfully implemented in primary educational contexts? The action research provided valuable insights into the complex area of teaching writing in the context of EFL, proving that its successful implementation will largely depend on the willingness of teachers to re-think their feedback-giving practice and embrace peer feedback as a part of their teaching routine.